The Effect of the Training Program about Management of Elders' Common Problems on the Level of Job Stress in Caregivers of Nursing Homes - Mahshid Forooghan; Danial Amanian; Mohammad Ali Hosseini (Golestan University of Medical Sciences, 2013)
Background and Objective: ‌With increasing older people population, the need to provide health care services in nursing homes is increasing. The aim of this study was to determine the effect of an educational program about the management of common problems in old age on the level of job stress in the caregivers of Golestan province nursing homes. Material and Methods: This pre-experimental study was conducted on all 24 caregivers (11 males and 13 females) working in the nursing homes of Golestan province. The valid and reliable instruments were a researcher-made questionnaire to evaluate the knowledge and Osipow's job stress questionnaire,‌ the intervention was an educational package to increase their knowledge and skills about the management of old age problems. The questionnaires were completed before, immediately after, one month and three months after the training. The data was analyzed by analysis variance, Pearson correlation, independent t-test and paired t-test. Results: With increasing the knowledge of the caregivers, a significant reduction in job stress scores (p<0.001) ‌was found after three months. Two components of job stress including overload (p<0.001) and insufficiency (p=0.002) showed significant decreases after three months compared to the mean scores before training. Conclusion: Due to The effect of training on stress reduction, providing comprehensive training programs for caregivers may lead to higher quality services and health promotion for both elders and their caregivers.